(untitled) (American Journal of Arts and Human Science, 2024)
The study focuses on the depiction of Islamophobia and nationalism in Egyptian cinema. The investigator conducted a thematic analysis by extracting seven research papers that elucidate the evolution of Egyptian cinema. Three themes through the data extracted have been identified: nationalism representation in Egyptian cinema, Islamophobia depiction and its influence in Egyptian cinema, and the intersection of Islamophobia and nationalism in Egyptian movies. The investigation further revealed how filmmakers navigate societal complexities, fostering dialogue and shaping perceptions. Also, the study focuses on Egyptian cinema’s role in promoting empathy, challenging stereotypes, and shaping the discourse. By having creative expression, movie makers contribute towards a compassionate and inclusive society that paves the way for understanding and social change.